Anaphylactic risk related to omalizumab, benralizumab, reslizumab, mepolizumab, and dupilumab. Issue 4 (3rd June 2021) - Li, Lisha; Wang, Zixi; Cui, Le; Xu, Yingyang; Guan, Kai; Zhao, Bin
Abstract: Background: Monoclonal antibodies (mAbs) are novel, effective therapeutics for the treatment of inadequately controlled severe asthma. Knowledge of the anaphylaxis risks related to different mAbs is essential for their appropriate and safe administration. This study aimed to evaluate the associations between different mAbs and anaphylactic reactions by applying statistical approaches to pharmacovigilance data. Methods: This was a retrospective study using data from the US Food and Drug Administration Adverse Event Reporting System database from January 2004 to September 2020. A total of 2006 reports of anaphylaxis related to benralizumab, dupilumab, mepolizumab, omalizumab, and reslizumab were obtained through data mining. The clinical characteristics of the cases were analyzed, and the risk signals of anaphylactic reactions and corresponding outcomes were investigated in the five mAbs. Results: The patients were mainly young and middle‐aged adults, with markedly more women than men. Omalizumab, benralizumab, reslizumab, and mepolizumab showed positive signals for anaphylaxis, while only dupilumab showed a negative signal. The risk of initial or prolonged hospitalization due to anaphylaxis was significantly higher in the benralizumab group than in the omalizumab group (42.86% vs. 28.92%, p = 0.024). Further, when anaphylaxis to omalizumab occurred, patients with asthma were more likely to have life‐threatening outcomes than those with chronic urticaria (18.0% vs. 12.9%, p = 0.022). Conclusion: In the current real‐world study, the positive anaphylaxis signals related to omalizumab, benralizumab, reslizumab, and mepolizumab suggested the need for the close monitoring of patients after drug use, and dupilumab showed a negative signal for anaphylaxis.